Grandmothers Behind the Scenes: Subordinate Integration, Care Work, and Power in Syrian Canadian Refugee Resettlement - Kahil, Rula; Iqbal, Maleeha; Maghbouleh, Neda (Refuge: Canada’s Journal on Refugees, 2022)
Research and policy concerning the Syrian Canadian diaspora has not prioritized elders. This article adds to scholarship about the well-being of newcomers admitted via the Syrian Refugee Resettlement Initiative through a focus on grandmothers resettled within their multigenerational families. Using interviews and qualitative field research, we show how the authority and status these elder women once held in Syria may be undermined by their comparatively subordinate integration in Canada. Although new, post-migration configurations of power, care work, and community may present some opportunities, the burdens and dependencies of subordinate integration mostly constrain these elders from reclaiming their authority and status.